1997
DOI: 10.1007/s004310050652
|View full text |Cite
|
Sign up to set email alerts
|

Management with a staged approach of the premature hydropic fetus due to complete congenital heart block

Abstract: This proposed staged approach with temporary epicardial leads can improve the outcome of hydropic fetuses due to complete congenital AV block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 8 publications
0
24
1
Order By: Relevance
“…One group proposed a staged approach to management, consisting of stimulating fetal lung maturation before Caesarian section, then treating the neonate with classic therapy for heart failure and heart block [18]. The difficult decision of whether and when to perform Caesarian section may best be done on a case-by-case basis.…”
Section: Therapymentioning
confidence: 99%
“…One group proposed a staged approach to management, consisting of stimulating fetal lung maturation before Caesarian section, then treating the neonate with classic therapy for heart failure and heart block [18]. The difficult decision of whether and when to perform Caesarian section may best be done on a case-by-case basis.…”
Section: Therapymentioning
confidence: 99%
“…Deloof et al [6] reported two preterm babies with anasarca. Isoprenaline was the initial treatment, followed by a trans-oesophageal stimulation until the resolution of the anasarca.…”
Section: Discussionmentioning
confidence: 98%
“…However, the response to these medications is usually insignificant, as evidenced in our patient. (3) In view of this, temporary pacing via the transcutaneous, epicardial or transvenous route is often instituted until the infant is of sufficient size for the permanent insertion of an epicardial pacing system. The decision to initiate temporary pacing in the present case was the low birth weight of the child, which precluded insertion of a permanent pacemaker.…”
Section: Discussionmentioning
confidence: 99%